2015
DOI: 10.1007/s00441-015-2122-y
|View full text |Cite
|
Sign up to set email alerts
|

β integrin-like protein-mediated adhesion and its disturbances during cell cultivation of the mussel Mytilus trossulus

Abstract: In this study, we focus on the specific contribution of β integrin-like protein to adhesion-mediated events in molluscan larval cells in culture that could not have been investigated within the whole animal. An analysis of disturbances to cell-substratum adhesion, caused by the integrin receptor inhibiting Arg-Gly-Asp-Ser (RGDS)-peptide, the Ca(2+)/Mg(2+)-chelators and the stress influence of freezing-thawing, reveals that all these factors resulted in the partial destruction of the integrin-extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In humans, α5β1, α8β1, αVβ1, αVβ3, αVβ5, αVβ6, αVβ8, and αIIbβ3 belong to the RGD-binding receptors, and they can be involved in cellular immunity, cell motility, cell proliferation, and cell differentiation through the interaction with RGDCP ( 3 ). In invertebrates, the accumulating evidences have revealed that RGDCP can also bind hemocytes and inhibit the cell activities in Botryllus schlosseri ( 79 ), Pacifastacus leniusculus ( 26 ), Lymnaea stagnalis ( 39 ), Mytilus trossulus ( 41 ), etc., suggesting the existence of RGD-binding integrins in such animals. In the present study, Cg α2 is phylogenetically clustered with the RGD-binding receptor, and it expectedly shows the binding activity to the RGD peptide by SPR analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, α5β1, α8β1, αVβ1, αVβ3, αVβ5, αVβ6, αVβ8, and αIIbβ3 belong to the RGD-binding receptors, and they can be involved in cellular immunity, cell motility, cell proliferation, and cell differentiation through the interaction with RGDCP ( 3 ). In invertebrates, the accumulating evidences have revealed that RGDCP can also bind hemocytes and inhibit the cell activities in Botryllus schlosseri ( 79 ), Pacifastacus leniusculus ( 26 ), Lymnaea stagnalis ( 39 ), Mytilus trossulus ( 41 ), etc., suggesting the existence of RGD-binding integrins in such animals. In the present study, Cg α2 is phylogenetically clustered with the RGD-binding receptor, and it expectedly shows the binding activity to the RGD peptide by SPR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although information regarding the evolutionary and functional relationships among invertebrate integrins is not clear, and limited by the few genome-sequenced species, more and more integrin family members are identified in non-model invertebrates, such as in the Mollusca, which is the biggest phylum in the marine animal kingdom with the most species. The molecular aspects of some integrins in mollusks such as Lymnaea stagnalis ( 39 ), Mytilus trossulus ( 40 , 41 ), B. glabrata ( 23 , 42 ), Mytilus galloprovincialis ( 43 ), and C. gigas ( 25 , 44 46 ) have been described, but the complete access to information regarding any of the mollusk species remains unavailable. The Pacific oyster ( C. gigas ), a sessile filter feeder exposed to a wide range of biotic and abiotic stresses, is an attractive model to study the diversity of immune receptor families and the mediation of associated immune responses in invertebrates ( 47 , 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Hemocytology and immunochemistry. All procedures for cell fixation and staining were described in detail in a previous study 41 . In brief, the cells were stained with TRITC-labeled phalloidin (Molecular Probes) and DAPI (Vector Laboratories) for visualization of actin cytoskeleton and nucleus.…”
Section: Dn Diagnostics Flow Cytometry Flow Cytometry Analysis and mentioning
confidence: 99%
“…These and other findings [36,46,47,54] have provided enough successful protocols for cryopreservation of marine invertebrate cells and larvae that will allow researchers to work with embryonic cells from these organisms throughout the year. The development of this field not only has environmental significance, but also offers great potential for marine biotechnology, as this field may clarify the cryoresistance mechanisms of marine organisms at ultra-low temperatures.…”
Section: Discussionmentioning
confidence: 95%